2009
DOI: 10.1177/1460408608101856
|View full text |Cite
|
Sign up to set email alerts
|

`Clearing' the cervical spine in conscious trauma patients

Abstract: This is a systematic review of published evidence regarding management of the cervical spine in conscious and co-operative trauma patients. We examine the literature in the following sections: clinical evaluation of the cervical spine; use of plain radiography; use of additional radiographic views; use of computed tomography; use of magnetic resonance imaging. Finally we consider the elderly and paediatric populations, particularly where there are significant differences compared to the general adult populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…A 2009 review also concluded that the alert, cooperative patient does not require immobilisation even if a clinical decision rule is positive, unless their conscious level deteriorates 12. They state that muscle spasm is a superior method to an artificial procedure.…”
Section: The Debatementioning
confidence: 99%
“…A 2009 review also concluded that the alert, cooperative patient does not require immobilisation even if a clinical decision rule is positive, unless their conscious level deteriorates 12. They state that muscle spasm is a superior method to an artificial procedure.…”
Section: The Debatementioning
confidence: 99%
“…A 2009 review also concluded that the alert, cooperative patient does not require immobilisation even if a clinical decision rule is positive, unless their conscious level deteriorates. 12 They state that muscle spasm is a superior method to an artificial procedure. The College of Emergency Medicine guidance emphasises the need for large-scale studies 13 while acknowledging the ethical conundrum that, “ the current practice … is so widely adopted and the consequences of causing or exacerbating a spinal injury so catastrophic that such trials may not be supported .”…”
Section: The Debatementioning
confidence: 99%
“…In a previous paper we presented the available evidence regarding cervical spine 'clearance' in the conscious and co-operative trauma patient (Blackham and Benger 2009). Clearance in unconscious patients is an even greater challenge because a key aspect of the clinical evaluation is absent, and therefore immobilisation may be maintained for long periods with an increased risk of complications.…”
Section: Aimmentioning
confidence: 99%